Analisis Kualitas Layanan dan Customer Relationship Management Pada BPJS Ketenagakerjaan Cabang Lombok Timur - Sofian Hadi; Bambang Triaji; Abdul Mukmin Rifai Yasin; Qori’atun Nazifah (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2026)
This study aims to analyze service quality and customer relationship management (CRM) practices in the context of public services at the East Lombok Branch of BPJS Ketenagakerjaan. In the public sector, CRM implementation cannot be understood solely as a managerial strategy, but rather as part of an effort to improve responsiveness and service quality to participants. This study used a qualitative approach with a descriptive-analytical design. Data were collected through in-depth interviews with BPJS Ketenagakerjaan employees and service participants, observations of the service process, and documentation studies of service procedures and media. The results indicate that CRM practices at BPJS Ketenagakerjaan East Lombok have supported improved access to information, communication with participants, and complaint handling. However, service quality still faces challenges in aspects of service consistency, human resource capacity, and participant understanding of the digital service system. These findings confirm that the effectiveness of CRM in public services is highly dependent on its integration with organizational governance and service orientation to the public interest